2019
DOI: 10.1177/0020731419842518
|View full text |Cite
|
Sign up to set email alerts
|

Leveling the Social Gradient in Health at the Local Level: Applying the Gradient Equity Lens to Norwegian Local Public Health Policy

Abstract: The gradient in health inequalities reflects a relationship between health and social circumstance demonstrating that health worsens as you move down the socioeconomic scale. Norway’s Public Health Act (PHA) specifically aims to tackle the gradient by addressing the social determinants of health. In this article, we draw on data from 2 studies that investigated how municipalities in Norway deal with these challenges. In doing so, we apply theoretical perspectives, as defined in the Gradient Evaluation Framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(33 reference statements)
1
9
0
1
Order By: Relevance
“…However, very few had an understanding that could be described as a gradient approach. Most respondents agreed that reducing health inequalities was important, but it was mostly described as developing policies and measures aimed at disadvantaged groups [17].…”
Section: Resultsmentioning
confidence: 99%
“…However, very few had an understanding that could be described as a gradient approach. Most respondents agreed that reducing health inequalities was important, but it was mostly described as developing policies and measures aimed at disadvantaged groups [17].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that only a select few LGs regarded health determinants a high priority ( 5 , 42 ). Behavioral and lifestyle programs were perceived to be of higher priority in LG compared to addressing determinants of health ( 43 , 44 , 71 , 83 ). The level of policy priority for addressing determinants of health was challenged by a range of factors including the political attraction to lifestyle programs ( 82 ), the perceived lack of urgency ( 45 ) and competing with priorities such as healthcare, food safety or other nationally determined priorities ( 44 , 46 , 72 , 83 ).…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral and lifestyle programs were perceived to be of higher priority in LG compared to addressing determinants of health ( 43 , 44 , 71 , 83 ). The level of policy priority for addressing determinants of health was challenged by a range of factors including the political attraction to lifestyle programs ( 82 ), the perceived lack of urgency ( 45 ) and competing with priorities such as healthcare, food safety or other nationally determined priorities ( 44 , 46 , 72 , 83 ). Larger municipalities in Norway were more likely to prioritize policies regarding living conditions, while smaller municipalities prioritized lifestyle issues ( 44 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing social inequalities and the differences in the opportunities that people have to improve their health is one of the major challenges faced in health promotion (Borrell & Pasarin Rua, 2004;Chesire, 2012;Reid, 2011;World Health Organization & UN-Habitat 2016). However, removing them is not easy because they are complex, with multiple structural causes and without simple, easy solutions (Fosse, Sherriff, & Helgesen, 2019).…”
Section: Introductionmentioning
confidence: 99%